PERLINDUNGAN HUKUM TERHADAP HAK KESEJAHTERAAN PEREMPUAN KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DI INDONESIA - Muhamad Sadi Is; Rr Rina Antasari; Qodariah Barkah (Mimbar Hukum, 2023)
Abstract Legal protection for the welfare rights of women victims of sexual violence in Indonesia is still very weak, whereas women’s welfare rights and sexual violence is a human rights issue that inherent arise from the moment humans are born. Without them, humans cannot live as human beings naturally and have civil and political rights, social, economic, and cultural rights as well as the right to develop. Therefore, the government passed Law Number 12 of 2022 concerning the Elimination of Sexual Violence, however, in its enforcement, there are still social obstacles. The problem is how legal protection for the welfare rights of women victims of criminal sexual violence in Indonesia guarantees humanitarian values. The research method used in this study is normative research which examines legal principles and Law Number 12 of 2022 concerning the Elimination of Sexual Violence. The conclusion reached is that the legal protection for the welfare rights of women victims of criminal acts of violence should apply dual delict, complaint delict and ordinary delict. In that case, the role of Komnas Perempuan is to design a solution that guarantees the welfare rights of women victims of sexual violence by coordinating with the LPSK and the minister for women and children to apply complaint offenses and ordinary offenses in their settlement. Abstrak Perlindungan hukum hak kesejahteraan perempuan korban kekerasan seksual di Indonesia dapat dikatakan masih sangat lemah, padahal hak kesejahteraan perempuan terhadap kekerasan seksual merupakan hak asasi manusia yang melekat secara alamiah sejak manusia dilahirkan. Tanpa hak asasi manusia, manusia tidak dapat hidup secara wajar dan memiliki hak sipil dan politik, hak sosial, hak ekonomi, hak budaya dan hak untuk berkembang. Ini merupakan alasan pemerintah mengesahkan Undang-Undang Nomor 12 Tahun 2022 tentang Penghapusan Kekerasan Seksual. Akan tetapi, di dalam penegakannya masih terdapat kendala sosial. Permasalahan yang sering terjadi ialah bagaimana perlindungan hukum terhadap hak kesejahteraan perempuan korban tindak pidana kekerasan seksual di Indonesia menjamin nilai-nilai kemanusiaan. Metode penelitian yang digunakan dalam studi ini ialah penelitian normatif yang meneliti mengenai asas-asas hukum dan Undang-Undang Nomor 12 Tahun 2022 tentang Penghapusan Kekerasan Seksual. Kesimpulan yang didapatkan menjelaskan bahwa perlindungan hukum hak kesejahteraan perempuan korban tindak pidana kekerasan sebagaimana diatur dalam Pasal 5-6 Undang-Undang Nomor 12 Tahun 2022 tentang Penghapusan Kekerasan Seksual seharusnya berlaku delik aduan dan delik biasa (dual delic), bukan hanya delik aduan. Oleh karena itu, peran Komnas Perempuan adalah mendesain penyelesaian permasalahan di atas yang menjamin hak kesejahteraan perempuan korban tindak pidana kekerasan seksual dengan berkoordinasi dengan LPSK dan menteri perempuan dan anak untuk memberlakukan delik aduan dan delik biasa di dalam penyelesaiannya.